2017
DOI: 10.1016/j.jvs.2016.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of thoracic endovascular aortic repair using aortic arch chimney stents in high-risk patients

Abstract: Introduction Aortic arch disease is a challenging clinical problem, especially in high-risk patients where open repair can have morbidity and mortality rates of 30–40% and 2–20%, respectively. Aortic arch “chimney”(AAC) stents used during thoracic endovascular aortic repair(TEVAR) are a less invasive treatment strategy than open repair, but the current literature is inconclusive about the role of this technology. The focus of this analysis is to describe our experience with TEVAR and AAC stent(s). Methods Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 39 publications
1
43
0
1
Order By: Relevance
“…Despite encouraging initial results, further studies are required to standardize this technique [19,20,21]. Chimney technique to extend the proximal landing zone in TEVAR is feasible in the majority of vascular centers, with satisfied midterm outcomes, but not without a risk of major complications [22][23][24][25]. Zhao et al [26] compared the outcomes of the chimney and hybrid technique for the reconstruction of a single arch branch and found that type Ia endoleak rate was significantly higher in the chimney group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite encouraging initial results, further studies are required to standardize this technique [19,20,21]. Chimney technique to extend the proximal landing zone in TEVAR is feasible in the majority of vascular centers, with satisfied midterm outcomes, but not without a risk of major complications [22][23][24][25]. Zhao et al [26] compared the outcomes of the chimney and hybrid technique for the reconstruction of a single arch branch and found that type Ia endoleak rate was significantly higher in the chimney group.…”
Section: Discussionmentioning
confidence: 99%
“… 41 New devices, such as fenestrated grafts, appear to be promising solutions to prevent occluding branches of the aortic arch, but more studies are needed to support the benefit of these devices. 42 43 …”
Section: Strokementioning
confidence: 99%
“…41 New devices, such as fenestrated grafts, appear to be promising solutions to prevent occluding branches of the aortic arch, but more studies are needed to support the benefit of these devices. 42,43 When proximal endograft coverage is needed and causes occlusion to the great vessels branching off of the aorta (►Fig. 3B), pre-TEVAR revascularization, in this case, a series of extra-anatomical bypasses, is required to maintain cerebral blood flow.…”
Section: Strokementioning
confidence: 99%